Development of smart painting machine using image processing - Saeed, Atif; Mithaiwala, Hussain Muslim; Hussain, Ammar Iqbal; Kumar, Tulsi (3C tecnología, 2020)
Painting is a process in automotive industry that takes about 10% of the total time consumed per vehicle. Currently, the painting lines in several automotive industries like Toyota motors or General motors is largely being automated after implementation of robotic arms. However, according to the study done, this automation is restricted to paint main body or chassis only, the coating and painting on small vehicle parts is still done manually. This paper represents the study conducted on local Toyota motor plant located in Karachi where the need of automating the small parts painting line evolved to increase production. The designed system is based on 3axis gantry mechanism which locates the position of parts to be painted on moving conveyor through computer vision, reach the coordinates, paints autonomously and forwards it to buffer station for drying. The computer vision is introduced to minimize the human interference and make the line semi-autonomous. The system was tested for correct image processing and at the end algorithms was correctly identifying and locating 90% of the parts. Moreover, the system was tested for one week in a laboratory environment and it was observed that production rate was increased to 2% as compare to their previously available data.